A three-year randomized clinical trial evaluating direct posterior composite restorations placed with three self-etch adhesives - Joseph Sabbagh; Layal El Masri; Jean Claude Fahd; Paul Nahas (Medical Journals Sweden, 2021)
Aim To compare the clinical performance of composite restorations placed with a universal adhesive, one-step and two-step self-etch adhesives in class I and II posterior cavities. Materials and methods In this in vivo study, 46 volunteers presenting with at least three carious lesions were included. Each participant received the three restorative systems: universal adhesive/nanofilled composite (Scotchbond Universal/Filtek Z350 XT: SBU/FZXT), one-step self-etch adhesive/microhybrid composite (G-aenial bond/G-aenial Posterior: GB/GP) and the two-step self-etch adhesive/nanohybrid composite (OptiBond XTR/Herculite Ultra: OBX/HU). The adhesives were all placed in self-etch mode. In total, 138 restorations were evaluated at baseline and at 6,12 and 36 months using the modified United States Public Health Service criteria. Data were analysed using Kruskal-Wallis, Mann-Whitney U, Friedman and Wilcoxon non-parametric tests (p < .05). Ninety-one restorations were evaluated at 36 months. Results Seven restorations, three SBU/FZXT, three GB/GP and one OBX/HU failed during this study. The reasons for failure were marginal fracture and secondary caries. SBU/FZXT restorations showed significant marginal deterioration in all parameters. Overall success rates were: 93.5% (SBU/FZXT), 96.6% (GB/GP) and 96.8% (OBX/HU). Conclusions After three years, the three restorative systems have comparable clinical effectiveness and success rates, except for the marginal integrity, that was suboptimal for both the SBU/FZXT and GB/GP restorations in comparison to the OBX/HU restorations.